Implementation of Parking Management Policies In The City of Cirebon - Fahreza, Rifqi; Hidayat, Moh. Taufik (Jurnal Polisci, 2026)
Background. Illegal parking remains a persistent urban governance issue in many Indonesian cities, including Cirebon, as it contributes significantly to traffic congestion, public disorder, and inefficient use of urban space. Despite legal frameworks such as Cirebon City Regulation No. 11 of 2019 on parking management, the implementation of parking control policies has not yet achieved optimal effectiveness. Aims. This study aims to analyze the implementation of parking management policies in the City of Cirebon, identify constraints in enforcement, and formulate improvement strategies to enhance policy effectiveness. Methods. A qualitative research approach was employed, using interviews, observations, documentation, and literature review as data collection methods. Data were analyzed through data reduction, data presentation, and conclusion drawing, while triangulation techniques were used to ensure data validity. The study adopts the policy implementation framework of Van Meter and Van Horn, which includes six dimensions: policy standards and objectives, resources, characteristics of implementing agencies, disposition of implementers, inter-organizational communication, and environmental factors. Result. The findings indicate that although institutional coordination and communication mechanisms are relatively adequate, policy implementation remains suboptimal due to limited human resources, inadequate facilities, weak enforcement consistency, and low public compliance with parking regulations. Social and economic factors also contribute to the persistence of illegal parking practices. Conclusion. Therefore, strengthening regulatory enforcement, improving public awareness, and enhancing institutional capacity are essential to achieving effective and sustainable parking management in urban areas.